Divorce Mediation Based on Maqashid Syari’ah - Muhamad Jamal; Ahmad Ashif; Syed Iftikhar Ali Gilani (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2024)
Divorce has become a significant social and legal issue in Indonesia, affecting not only couples but also children and extended families. This study explores the role of judges in increasing the success rate of divorce mediation at the Temanggung Religious Court in 2022–2023, using the framework of Maqashid Syari’ah as a guiding principle. The research employs a qualitative approach with data collected through interviews, observation, and document analysis. Findings reveal that judges employ strategies that integrate religious, familial, and social considerations, emphasizing sincerity, the caucus method, and recalling positive marital experiences to facilitate reconciliation. While mediation cannot always restore the marital relationship, it effectively protects the five essential objectives of Maqashid Syari’ah: religion, life, intellect, progeny, and wealth, ensuring that the parties separate amicably and without lingering resentment. This study demonstrates that applying Maqashid Syari’ah in divorce mediation contributes to more ethical, fair, and socially responsible outcomes, offering a model for improving dispute resolution in Islamic family law.